DNA Uptake by Type IV Filaments - Piepenbrink, Kurt H. (Frontiers in Molecular Biosciences, 2019)
Bacterial uptake of DNA through type IV filaments is an essential component of natural competence in numerous gram-positive and gram-negative species. Recent advances in the field have broadened our understanding of the structures used to take up extracellular DNA. Here, we review seminal experiments in the literature describing DNA binding by type IV pili, competence pili and the flp pili of Micrococcus luteus; collectively referred to here as type IV filaments. We compare the current state of the field on mechanisms of DNA uptake for these three appendage systems and describe the current mechanistic understanding of both DNA-binding and DNA-uptake by these versatile molecular machines.